Cynical References to Political Correctness in Hungarian Media in the 2000s - Erzsébet Barát (Hungarian Cultural Studies, 2011)
In this paper I analyze the strategy in Hungarian public discourse for discrediting feminism in the media in the early 2000s. The strategy consists in the systematic conflation of feminism with the demand for “politically correct” language. My analysis will show that the motivation for the conflation occurs, on the one hand, in the name of tolerance or, on the other, to the determent of feminism. These apparently very different discourses, however, overlap and are effects of the same strategy of discreditation. They both rest on the assumption that feminism is an exclusionary ideology hence it is to be tolerated at best, or to be fought mercilessly. Despite the apparent opposition between the two approaches, their goals are the same. The reduction of feminism to political correctness and its representation as the manifestation of some general practice of ‘language cleansing’ “benignly” masks the real object of feminist language criticism, namely, sexist and homophobic exclusionary language use and their symbolic and material consequences. These are found everywhere in contemporary Hungary. I shall argue that the alarming similarity of the two perspectives is a recent phenomenon in Hungarian public discourse that emerged in the first decade of the millennium. It replaces the strategy of the 1990s that represented feminism as a matter of some individual and isolated efforts and as such eventually harmless on a social scale. The turn of the first decade re-imagines feminism as a social practice that is argued to be an intolerant or aggressive attempt at purging language use. This change in the meaning of the concept is caused in part, I shall argue, by the stereotypical conceptualization of language use itself. The concept is stereotypical in that it draws on (value) judgments expected to be understood as self-evident hence able to preempt any need for reflexivity on the part of the reader.